2016
DOI: 10.1177/0042098015612983
|View full text |Cite
|
Sign up to set email alerts
|

Life in an Alpha Territory: Discontinuity and conflict in an elite London ‘village’

Abstract: This paper forms part of a larger study of the social implications of London becoming the location of choice for the global 'super-rich'. The study examines how members of new wealth elites organise their day-to-day activities and the impact their growing numbers have on the prestigious neighbourhoods from which they are displacing pre-existing elites, and the disruptive effect they have on previously taken-for-granted mores, networks and places of association. The aim of the paper is to situate this wider stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…These groups have very different socio-spatial experiences in the city, they will interact with local infrastructure in different ways (if at all), and will, thus, impact and engage with the city in different ways (see also : Forrest, Koh, & Wissink, in press-b). In London, for example, neighbourhoods with high concentrations of HNWI and UHNWI investors may appear to be (or may be) devoid of people, and local businesses can become unviable in these neighbourhoods (Webber & Burrows, 2016), to say nothing about the broader questions relating to neighbourhood life.…”
Section: Investor Cohorts and Property Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…These groups have very different socio-spatial experiences in the city, they will interact with local infrastructure in different ways (if at all), and will, thus, impact and engage with the city in different ways (see also : Forrest, Koh, & Wissink, in press-b). In London, for example, neighbourhoods with high concentrations of HNWI and UHNWI investors may appear to be (or may be) devoid of people, and local businesses can become unviable in these neighbourhoods (Webber & Burrows, 2016), to say nothing about the broader questions relating to neighbourhood life.…”
Section: Investor Cohorts and Property Typesmentioning
confidence: 99%
“…Many HNWI, UHNWI and UUHNWI go to great lengths to protect their privacy and to isolate themselves from public scrutiny. Recent studies have shown that gaining access to the economic, social and political spaces of the HNWI, UHNWI and UUHNWI can be a difficult task, with each group presenting different challenges (see the following authors for methodologies suited to HNWI, UHNWI and UUHNWI studies: Atkinson, 2016Atkinson, , p. 1309Harrington, 2016, p. 22;Webber & Burrows, 2016).…”
Section: Investor Cohorts and Property Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…A particular feature of contemporary wealth formations is their almost free-floating position above the wider social mass and physical fabric of the city (Graham, 2016) and which has displaced the codes and, in some cases, physical position of a more patrician, aristocratic and monied elite which offered a more reciprocal, engaged and connected form of patronage (Webber and Burrows, 2016). The kind of business elite exit from civic life identified by Lasch (1995) began to mark a new kind of relationship between an increasingly wealthy fraction of a nouveau riche class who had been fattened under neoliberalism and the accrual of gigantic rewards for work in finance, banking, insurance and real estate.…”
mentioning
confidence: 99%